Descriptive analysis of physical and sports practice and interests in school 5th and 6th primary - Borrego Balsalobre, F. J.; Carrillo García, A. B.; Díaz Suárez, A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2015)
The aim of this study was to analyze the thought that students have in Physical Education and its practical interests. For this, the Inventory of Habitual Physical Activity for School (IAFHE) to a total of 35 students from two schools in the region of Murcia was used. The sample was showed that the vast majority of them practiced outside school year but insufficient as established by the recommendations of international institutions times.